A197 PREVALENCE OF PRIMARY BILIARY CHOLANGITIS IN CANADA: FIRST NATIONAL STUDY. (1st March 2018) - Yoshida, E M; Fischer, A; Mason, A; Shah, H; Peltekian, K M; Hux, M; Thiele, S L; Borrelli, R
Abstract: Background: Primary biliary cholangitis (PBC) is a rare, progressive autoimmune liver disease that can result in significant morbidity, need for liver transplant, and premature mortality. Prevalence of PBC has been found to vary by geography and to be increasing over time. The only recent Canadian estimate is for Alberta where prevalence in 2001 was reported to be 227 cases per million. Aims: Based on gaps in the existing PBC literature, we undertook this study to provide the first national and regional prevalence estimate of PBC in Canada. Methods: The 2015 prevalence of PBC in Canada was estimated using longitudinal patient-level records of the Discharge Abstract Database and National Ambulatory Care Reporting System from the Canadian Institute for Health Information. Cases were identified using a PBC diagnosis (International Classification of Diseases Version 10 - Canadian Edition K74.3) between 2007 – 2015 at any hospital visit (acute care admission, same-day surgery, emergency department or hospital-based specialty clinic). Cases deceased prior to 2015 were excluded. Quebec records were not available for study. Although all Canadian hospitals report acute care admissions, as the proportions reporting other hospital-based services differ by province, crude case counts were projected to complete coverage. Prevalence estimates were age and gender adjusted to the 2015 Canadian population. The 2013 prevalence was estimated using the same methodology. Persons with late stage PBC were identified using late stage-related diagnoses. Results: The Canadian 2015 annual prevalence of PBC managed in a specialty clinic or visiting hospital was 318 (95%CI 309–327) cases per million. By region, prevalence per million estimates were: British Columbia 327 (95%CI 302–352); Alberta 292 (95%CI 275- 309); Prairie provinces 399 (95%CI 360–438); Ontario 283 (95%CI 269–297); and the highest prevalence of 465 (95%CI: 426, 504) was seen in Maritime provinces. PBC cases were predominantly female (78%), and the majority were aged 40 to 64 (54%), or over 65 years of age (39%). The 2013 prevalence of PBC was estimated to be 256 (95%CI: 248, 264) cases per million. PBC was classified as advanced stage for 29% (95%CI: 26%, 32%) of patients. Conclusions: This study reports the first national prevalence for Canada and geographic regions, and provides an important basis for understanding the magnitude of disease in Canada. From 2013 to 2015, the prevalence of PBC remains increasing. Atlantic Canada appears to have the highest burden of PBC in the country. Funding Agencies: None